Access to a newly adapted diabetes-specific multimodal cross-sectoral and interdisciplinary psychotherapeutic care option for a high-risk group of patients with diabetes mellitus and distress : protocol for the minDBe pilot study - Zara, Sandra; Kruse, Johannes; Kampling, Hanna; Justus Liebig University Giessen (My University, 2025)
Background: Diabetes is a chronic disease requiring daily self-management to regulate physiological parameters like glycemic control. Despite extensive training being available, most patients with diabetes do not meet their target blood sugar levels. Moreover, diabetes-related emotional distress and psychological burden in the form of depressive and anxiety symptoms are very common. Patients with these challenges represent a high-risk group in terms of increased morbidity, mortality, and health care costs as well as decreased quality of life. Hence, in addition to somatically focused standard care, this patient group requires specific treatment options that also address psychosocial aspects. However, these treatments are often not available in routine care. Psychosomatic outpatient clinics (PsIAs) could address this gap by offering multimodal and integrative treatment. However, the indication for treatment in PsIAs and the referral pathways for patients with diabetes from practices or diabetes clinics to PsIAs remain complicated. Moreover, specific treatment options must be adapted. Objective: This study aims to assess the needs for referral pathways to PsIAs from the patient and service provider perspectives and to adapt the already effective psychosomatic intervention psy-PAD for a group setting (psy-PADGroup), fitting the multimodal PsIA structures. Methods: This pilot study comprises an explorative qualitative design based on a multilevel approach, using 2 work packages: work package 1 assesses the patient perspective (n=40) using focus groups, as well as the service provider perspective with interviews (n=30). Work package 2 comprises an expert workshop with clinicians and patient representatives (n=10) to adapt the psy-PADGroup manual for the modalities of PsIAs. We will audio-record the patient focus groups and service provider interviews. The audio recordings will be transcribed and analyzed using content analysis within the framework of interpretative text evaluations with MAXQDA. Results: Outcomes will be (1) the needs regarding referral pathways, (2) short questionnaires to economically assess the acceptance and feasibility of the referral pathways in preparation for the minDBe main study, and (3) the adapted psy-PADGroup intervention for an interdisciplinary multimodal treatment option to be implemented in the structures of PsIAs. Conclusions: The minDBe pilot study will lay the foundation for the minDBe main study, which aims to evaluate the psy-PADGroup as part of an interdisciplinary multimodal psychotherapeutic treatment program in a randomized controlled trial.
Keywords: ddc:610